Islamic logic in the collection of Ibn Sahl al-Andalusi (Journal of the College of Basic Education, 2022)
The research was not limited to the descriptive approach or the theoretical framework; Rather, it is linked to Islamic behaviorEach image has its behavioral impact and its applied aspect in the reality of life.” After we pondered the Diwan of Ibn SahlThe Andalusian Seville, and our guarana in his personal behavior with that overwhelming spirit that walked in his beingAfter his conversion to Islam and his highness from the troubled reality of man to reassurance and confidence. That can be saidImmunity of faith in the heart of the poet; made him more great and gave him a destiny; Not to mention the intellectual cultureAnd Islamic literature that I enjoy.This issue is rarely encountered in our Andalusian literary history, and it is an issue that needs to be addressedto a lot of deliberation and caution, starting with the doubt that surrounded his conversion to Islam; Which urges us to contemporarysome researchers; The search for an introduction and preface has grown.